Criteria for Early Diagnosis and Treatment of Candidiasis of the Oral Mucosa (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The analysis of special literature devoted to the relationship of diseases of candidiasis of the oral mucosa is carried out.Based on the above data, the authors came to the conclusion that candidiasis of the oral mucosa has not been studied enough and further scientific research is required.